2001
DOI: 10.1046/j.1528-1157.2001.41300.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Levetiracetam in Children

Abstract: Summary:Purpose: The pharmacokinetics of the novel antiepileptic drug (AED) levetiracetam and its major metabolite, ucb L057, were studied in children with partial seizures in a multicenter, open-label, single-dose study.Methods: Twenty-four children (15 boys, nine girls), 6 to 12 years old, received a single dose of levetiracetam (20 mg/kg) as an adjunct to their stable regimen of a single concomitant AED, followed by a 24-h pharmacokinetic evaluation.Results: In children, the half-lives of levetiracetam and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
115
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 12 publications
16
115
1
3
Order By: Relevance
“…The pharmacokinetic profile in pediatric patients shows that levetiracetam is cleared more quickly and also shows significant interindividual variability (16). Therefore, pediatric patients require higher dosage, and it is crucial to measure the amount of drug in patient's blood for effective treatment (16,17). Apart from evaluating toxicity, therapeutic drug monitoring for levetiracetam is used in adjusting dosage for renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic profile in pediatric patients shows that levetiracetam is cleared more quickly and also shows significant interindividual variability (16). Therefore, pediatric patients require higher dosage, and it is crucial to measure the amount of drug in patient's blood for effective treatment (16,17). Apart from evaluating toxicity, therapeutic drug monitoring for levetiracetam is used in adjusting dosage for renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, normal levels of SV2 and synaptotagmin at the synapse are maintained, which may lead to reduce seizures (1,3). Also, it is suggested that LEV partially inhibits N-type high-voltage-activated Ca 2+ currents and reduces the release of Ca 2+ from intraneuronal stores (4)(5)(6)(7)(8)(9). LEV has a favorable pharmacokinetic profile.…”
Section: Contextmentioning
confidence: 99%
“…Наличие раствора для приема внутрь -очень большой плюс, принципиально отличающий кеппру от других ПЭП и дженериков левети-рацетама [47,54,56,57]. Имеющиеся в настоящее время данные о применении леветирацетама позволяют реко-мендовать его также для стартовой монотерапии юноше-ской миоклонической эпилепсии у женщин [53,58].…”
Section: эпилепсия у детейunclassified